Comparison of interscalene brachial plexus block and intra-articular local anesthetic administration on postoperative pain management in arthroscopic shoulder surgery - Aksu,Recep (2015)
BACKGROUND AND OBJECTIVES: In this study, the aim was to compare postoperative analgesia effects of the administration of ultrasound-guided interscalene brachial plexus block and intra-articular bupivacaine carried out with bupivacaine. METHODS: In the first group of patients 20 mL 0.25% bupivacaine and ultrasound-guided interscalene brachial plexus block (ISPB) were applied, while 20 mL 0.25% bupivacaine was given via intra-articular (IA) administration to the second group patients after surgery. Patients in the third group were considered the control group and no block was performed. Patient-controlled analgesia (PCA) with morphine was used in all three groups for postoperative analgesia. RESULTS: In the ISPB group, morphine consumption in the periods between 0-4, 6-12 and 12-24 postoperative hours and total consumption within 24 h was lower than in the other two groups. Morphine consumption in the IA group was lower than in the control group in the period from 0 to 6 h and the same was true for total morphine consumption in 24 h. Postoperative VASr scores in the ISPB group were lower than both of the other groups in the first 2 h and lower than the control group in the 4th and 6th hours (p < 0.05). In the IA group, VASr and VASm scores in the 2nd, 4th and 6th hours were lower than in the control group (p < 0.05). CONCLUSION: Interscalene brachial plexus block was found to be more effective than intra-articular local anesthetic injection for postoperative analgesia.